1981
DOI: 10.1128/jcm.13.1.80-84.1981
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Vibrio cholerae protease activities with peptide digest analysis

Abstract: A simple method for the analysis of microbial proteases is described that was used to characterize the proteolytic activities of various Vibrio cholerae isolates. This method utilized the unique peptides generated from the degradation of a standard protein by proteases of various specificities. These peptides were anaâ lyzed by sodium dodecyl sulfate-polyacrylamide gel electrophoresis. The unique patterns of peptides seen in gels can be used to type proteases according to their relative specificities. Culture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
3
0

Year Published

1982
1982
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 7 publications
1
3
0
Order By: Relevance
“…Our results are in agreement with previous reports on the wide variation in extracellular protease production among different strains of V. cholerae (11,24). Among V. cholerae El Tor isolates, we found a 100-fold variation in protease production, and the two classical strains we tested differed by a factor of 80.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our results are in agreement with previous reports on the wide variation in extracellular protease production among different strains of V. cholerae (11,24). Among V. cholerae El Tor isolates, we found a 100-fold variation in protease production, and the two classical strains we tested differed by a factor of 80.…”
Section: Discussionsupporting
confidence: 93%
“…Serological analysis will be of use in the further investigation of this phenomenon. Schneider et al (24) have also reported the occurrence of two different molecular weight forms of type II protease activity. Serological and biochemical evidence presented by these authors (24) indicates that type II protease is widespread among V. cholerae strains, and our own results have shown that it is the dominant activity in all the high and medium protease producers so far investigated.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Only one V. cholerae extracellular protease gene, the soluble hemagglutinin/protease (hap) (12), has been cloned and sequenced to date. However, the biochemical characterization of extracellular proteases from V. cholerae suggests the existence of more than one type of protease (24,32). Furthermore, hap-deficient mutants have shown residual proteolytic activity that was not inhibited by anti-hemagglutinin/protease (anti-HA/P)-specific antiserum (12).…”
mentioning
confidence: 99%